Water consumption in Germany [dataset] - Tosun, Jale; Debus, Marc; Bulian, Simon; Klein, Sina; Scherer, Ulrike; Goeschl, Timo; Horn, Harald (Universität, 2024)
This dataset contains information collected via a survey of 5815 respondents based in Germany on their water drinking habits. The data was collected in September 2021 by the company Bilendi & Respondi.
Gefördert durch: Ministry of Science, Research and Arts for the State of Baden- Württemberg: Grant No. 33-7533.-25-11/31/31
Gesehen am 26.11.2024
Keywords: Forschungsdaten; Datenbank